Peran Teori Chomsky dalam Evolusi Psikolinguistik Modern : Fokus Historis dan Teoritis yang Mendalam - Musawir, Ahmad; Patara, Anggitha; Muhkmar, Ulfah; Dewi, Anita Candra (JURNAL EDUKASI NONFORMAL, 2025)
This article examines Noam Chomsky’s pivotal role in shaping modern psycholinguistics through his transformational-generative grammar theory and the concept of Universal Grammar. The study highlights the shift from a behaviorist view of language acquisition—centered on the stimulus-response model—to a cognitive-biological framework that views language as an innate faculty in the human mind. The aim of this study is to explore Chomsky’s theoretical contributions and their impact on the evolution of psycholinguistics as a multidisciplinary field integrating linguistics, psychology, and neuroscience. Using descriptive qualitative methods through literature review, this study analyzes key concepts such as the Language Acquisition Device (LAD), mental modularity, and the relationship between language and brain structure. The results show that Chomsky’s theories not only challenge previous linguistic paradigms but also provide a strong theoretical foundation for contemporary studies in language processing, language education, and biolinguistics. His thinking continues to be influential in understanding language as both a cognitive process and a fundamental biological capacity in humans.